Biomechaniceskie osobennosti techniki tjaželoatleticeskogo ryvka u mužcin i ženšci - Nopin, S. V.; Koryagina, Yu. V.; Ter-Akopov, G. N.; Abutalimova, S. M.; Kopanev, A. N. (Vestnik sportivnoj nauki; Sports science bulletin, 2021)
The aim of the work was to reveal gender differences in the technique of weightlifting snatch fulfillment among highly qualified athletes in conditions of training activity. The study involved 45 male and female weightlifters, highly qualified, members of the Russian Federation national weightlifting team. The work was carried out on the BTS Motion System (BTS Bioengineering, Italy), which includes SMART-DX - an optoelectronic system with three infrared cameras and two video cameras, two sensor floor strain-dynamometric platforms measuring 60×40 cm. To analyze the weightlifting snatch technique, computer programs were developed. To analyze the technique, the phase structure of the weightlifting snatch was used according to L.S. Dvorkin. The results of the study showed regular gender differences associated with greater strength and speed capabilities of men and expressed in large indicators of the strength of support reactions, the rate of their growth, power, and the speed of the barbell movement. Women are not inferior to men in terms of kinematic characteristics, dynamics of amplitude in the joints, movements of the bar in the horizontal plane and sometimes show great speed and amplitude of flexion of the knee and ankle joint. The length of the trajectory of the barbell movement is longer in men, which is associated with greater growth. These differences in technique must be taken into account when evaluating the snatch technique. For each indicator, taking into account sex differences, model characteristics of the biomechanical indicators of the snatch technique for men and women were developed.